Pemberdayaan Kesehatan Santri Tentang Pemberian Tablet Fe Dan Gizi Seimbang Sebagai Upaya Pencegahan Anemia Dengan Media Animasi - Natalia, Shanty; Lestari, Yusri Dwi; Marhamah, Siti; Talu Ate, Marniati Dumedri; Kaka, Stefania Ambu; Andika Putri, Uswara Sri; Kobak, Uwera; Elsy Diaz, Angelina; Dawapa, Yuliana; Asmara, Rita puji (Yayasan Inspirasi El Burhani, 2025)
Introduction: Anemia in adolescent girls often occurs due to iron deficiency, which can affect health and daily activities, including academic performance. Therefore, education on the importance of balanced nutrition and iron tablet consumption is carried out through interactive, engaging, and easily understandable animation media. Objective: This community service activity aims to empower female islamic boarding school students at Nurul Jadid Junior High School, Paiton District, Probolinggo Regency, in preventing anemia through the administration of iron tablets and the application of balanced nutrition. Method: The activity began with a counseling session about the symptoms of anemia, its impact on the body, and how to prevent it through a healthy diet and the consumption of iron tablets. The counseling was delivered using animation media, followed by a discussion session to deepen participants' understanding and hemoglobin level testing. In addition, the female islamic boarding school students were provided with iron tablets periodically as a direct form of support for preventing anemia. Result: The results of this activity showed an increase in the female islamic boarding school students understanding of the importance of balanced nutrition and iron tablet consumption. Participants gained a better understanding of how to avoid anemia and how to maintain good health with the right diet. The use of animation media proved to be effective in delivering information in a fun and easily comprehensible way for adolescent girls. Conclusion: This activity have a positive impact on the health of the female islamic boarding school students and serve as a model for other community service initiatives in efforts to prevent anemia in adolescents.